Morphological Characterization of Brown Algae Turbinaria sp From The Coastal Water of Aboru Village Central Maluku - Maria Riry; Hermalina Sinay; Ritha Lusian Karuwal (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2022)
The coastal water of Aboru village is one site with high diversity of marine biological resources such as brown algae. The purpose of this study was to determine the morphological character of the brown algae Turbinaria from the coastal water of Aboru Village. The procedure consists of field collection, and observations in the laboratory. The morphological characters observed were the presence/absence of rhizoid/holdfast, cauloid/stipe, phylloid/blades, and presence/absence of pyrenoid/vesicle (air bubbles), thallus length, phylloid length, and thallus branching type. The data obtained were analyzed descriptively. The results showed that there were three types of Turbinaria, namely T. ornata, T. decurens, and T. conoides. All species have rhizoids, cauloids, and phylloids, while pyrenoids are only found in T. ornata. The branching type of T. ornata and T. decurens is sympodial, while T. conoides have monopodial branching type. In the conclusion, there were litle morphological variations in the genus Turbinaria found in the coastal water of Aboru Village.